Culture-oriented strategies of Akhmet Baitursynov – translator of Alexander Pushkin’s fairy tales (Eurasian Journal of Philology Science and Education, 2022)
The article is devoted to the translations of «The Tale of the Fisherman and the Fish» and «The Tale of the Golden Cockerel» by Alexander Pushkin by Akhmet Baitursynov. A model of culture-oriented strategies in Baitursynov’s translation experience is proposed. Popularization of the fairy tale of the Russian writer and adaptation to the perception of the Kazakh reader required the identification of factors of the translator’s choice of a certain strategy. The analysis of the correlation of the cultural grid, domestication, foreignisation and estrangement allowed us to establish their connection with the authenticity of literary translation. The study of Baitursynov’s translation skills was carried out in the aspect of the correlation of the plot syntagma and the paradigmatic plot. This approach contributes to the study of the author’s impact on the reader. The obtained results of the study complement the picture of the Kazakh literary process from the point of view of the relationship between culture-oriented translation strategies and the development of a literary fairy tale in Kazakh culture. Kazakhstan’s Pushkiniana is being replenished. The analysis of culture-oriented strategies revealed the connection with the authenticity of literary translation. The use of tacosnomic, statistical, formal and comparative-typological methods contributed to the establishment of the unity of the Baitursynov-translator method. The idea of estrangement as a form of domestication is substantiated, the predominance of domestication is explained in order to popularize Pushkin’s fairy tale and adapt it to the perception of the recipient of the translation. The essence of exclusion as a result of the influence of the national conceptual sphere on the author’s is proved. The study of domestication and foreignisation was carried out in the aspect of their connection with the plot syntagma. A connection has been established between the paradigmatic nature of the original plot and the use of estrangment in translation. The analysis of the translation variance helps to supplement the idea of the factors of integration of the original into the culture of the target language. The model of culture-oriented strategies expands the scientific and methodological arsenal of literary translation studies, contributes to the addition of historical and theoretical poetics of Kazakh literary studies, the development of literary studies with linguo conceptology, linguopragmatics. The practical significance of the work is due to the inclusion of translations of Pushkin’s fairy tales by Baitursynov in the collection of works of the Russian writer in the Kazakh language, which contributes to the integration of the results of science into publishing. The results obtained make it possible to systematize recommendations for new translators of Pushkin’s fairy tale